Assessing disease activity in psoriatic arthritis: a literature review - Tucker, L; Coates, L; Helliwell, P (Springer, 2018)
Psoriatic arthritis (PsA) is a multifaceted disease, with a high impact on patients’ psychological and physical well-being. There is increasing recognition that assessment of both clinical aspects of disease and patient identified concerns, such as fatigue, work disability, and treatment satisfaction need to be addressed. Only then can we fully understand disease burden and make well-informed treatment decisions aimed at improving patients’ lives. In recent years, there has been much progress in the development of unidimensional and composite measures of disease activity, as well as questionnaires capturing the patient’s perspective in psoriatic disease. Despite these advances, there remains disagreement amongst clinicians as to which instruments should be used. As a consequence, they are yet to receive widespread implementation in routine clinical practice. This review aims to summarize currently available clinical and patient-derived assessment tools, which will provide clinicians with a practical and informative resource.